Communities of the earthworms (Oligochaeta: Lumbricidae) in the soil of various plant associations of the Skopje valley, Macedonia - Šapkarev, Jonče (Macedonian Journal of Ecology and Environment, 1994)
In this artical species composition, density of populations and vertical distribution of the lumbricid fauna in the soils from six various plant associations of Skopje’a valley are given. Comparison of the eartworm communities in the various types of soils is made. Finally,some of more important environmental factors of the explored soils are presented.